Resolving China's Energy Trilemma: Nuclear Power Synergy in the Dual-Carbon Transition - Gao Shuaihang; Li Shangyu; Wang Zhengyang (MATEC Web of Conferences)
China currently accounts for the largest share of global CO₂ emissions, faces immense pressure to achieve its “dual-carbon” goals amid a coal-dominated energy structure and rising emissions. The energy trilemma theory highlights inherent conflicts among energy security, affordability, and sustainability, yet existing studies inadequately address regional heterogeneity and dynamic synergies. This study evaluates China’s energy transition pathways by analyzing the trade-offs and synergies of photovoltaic, wind, and nuclear power within the trilemma framework. Through a comparative analysis of technical efficiency, economic costs, and environmental impacts, we demonstrate that nuclear power outperforms renewables in stability (7,805 annual utilization hours vs. 2,127 for wind), cost-effectiveness (¥0.28/kWh levelized cost), and near-zero emissions. Despite challenges in waste management and public acceptance, nuclear energy’s high energy density and grid reliability position it as a critical solution for balancing the trilemma. The findings advocate for prioritizing advanced nuclear technologies and stringent regulatory frameworks to accelerate decarbonization while ensuring energy security.